The Impact of Pneumatic Chemistry on Robert Southey's Madoc. Issue 6 (1st November 2016) - Colman, Adam
ABSTRACT: This essay considers the effects of Robert Southey's encounters with pneumatic chemistry on his epic Madoc . The 1797–1799 draft of the poem describes air differently from the published 1805 version, which was extensively revised in the years following Southey's experiences with nitrous oxide at the Pneumatic Institution. Matter, in general, appears particularly fraught and complex in the 1805 Madoc —specifically, an emphasized metonymic materiality there links to unstable metaphoric resonances. Examining Southey's response to nitrous oxide along with the work of pneumatic chemists and the 1805 Madoc 's descriptions of material experience, this essay argues that Southey developed Madoc 's formal complexities in light of new senses of materiality he arrived at with regard to pneumatic chemistry.